CMV-independent increase in CD27−CD28+ CD8+ EMRA T cells is inversely related to mortality in octogenarians - Martin-Ruiz, Carmen (NPJ Aging Mech Dis, 2020)
Cytomegalovirus (CMV) seropositivity in adults has been linked to increased cardiovascular disease burden. Phenotypically, CMV infection leads to an inflated CD8 T-lymphocyte compartment. We employed a 8-colour flow cytometric protocol to analyse circulating T cells in 597 octogenarians from the same birth cohort together with NT-proBNP measurements and followed all participants over 7 years. We found that, independent of CMV serostatus, a high number of CD27−CD28+ CD8 EMRA T-lymphocytes (TEMRA) protected from all-cause death after adjusting for known risk factors, such as heart failure, frailty or cancer (Hazard ratio 0.66 for highest vs lowest tertile; confidence interval 0.51–0.86). In addition, CD27−CD28+ CD8 EMRA T-lymphocytes protected from both, non-cardiovascular (hazard ratio 0.59) and cardiovascular death (hazard ratio 0.65). In aged mice treated with the senolytic navitoclax, in which we have previously shown a rejuvenated cardiac phenotype, CD8 effector memory cells are decreased, further indicating that alterations in T cell subpopulations are associated with cardiovascular ageing. Future studies are required to show whether targeting immunosenescence will lead to enhanced life- or healthspan.